Algoritmo tabu search especializado para o problema de planejamento da expansao de sistemas de transmissão - Khorasani, Hamid [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Transmission system plays an undeniable role to avoid load shedding, black out, etc. by supplying the power to all type of consumers under critical circumstances. A transmission network expansion planning (TNEP) enables a network to transmit enough generated power to load centers at a specified times to satisfy the increased electric power demand. In TNEP problem, in addition to satisfying all the technical constraints, an economic plan is demanded. The expansion of transmission network is one of the initiatives, in which the necessary decisions are made and planned at the national level to absorb significant financial resources. Therefore, planning for an optimal expansion project with the least cost and highest reliability is a crucial task. From the viewpoint of the structure of power systems, it can be stated that TNEP is analyzed in both regulated and deregulated environments. The main objective of TNEP in a regulated environment is to meet the load demand at the least cost while the reliability criterion is taken into account. On the other hand, in restructured power systems, the transmission expansion is primarily intended to create a competitive environment without any discrimination to access to the transmission network. This can perfectly ensure competitive markets. In general TNEP problem in regulated environments is a non-linear mixed integer programming problem, which subjects with some difficulties, such as the time- consuming nature of the problem as well as the need for a non-convex optimization technique. In addition, due to the complicacy of the combinatorial optimization problems and also, since there exist many local minima for this problem, it is considered as a time- consuming problem. Moreover, since the conventional mathematical programming methods do not necessarily work very satisfactorily, therefore, various meta-heuristic optimization techniques have been examined for this problem. However, the scope and ...

O sistema de transmissão desempenha um papel muito importante na prevenção de cortes de cargas, blecaute (colapso), etc., fornecendo energia para todos os tipos de consumidores e às vezes em circunstâncias críticas. O problema de planejamento de expansão de sistemas de transmissão (PET) possibilita que a rede transmita a energia gerada para abastecer os centros de carga em todo instante de tempo, a fim de satisfazer a crescente demanda por energia elétrica. No problema PET, além de cumprir com todas as restrições técnicas, deve-se elaborar um plano de expansão econômico. O planejamento da expansão do sistema de transmissão é um tipo de atividade em que as decisões devem são tomadas e planejadas em nível nacional já que implica absorver recursos financeiros significativos. Consequentemente, elaborar um projeto de expansão ideal, com o mínimo custo possível e com a máxima confiabilidade é uma tarefa crucial. Do ponto de vista da estrutura dos sistemas de energia, pode-se afirmar que o problema PET é analisado nos sistemas regulados e desregulados. O principal objetivo do PET em um ambiente regulado é atender a demanda de carga, com mínimo custo, levando em consideração o critério da confiabilidade. Por outro lado, em sistemas de energia reestruturados, a expansão da transmissão destina-se a criar um ambiente competitivo sem qualquer discriminação de acesso à rede de transmissão. Esse mecanismo pode perfeitamente assegurar mercados competitivos. Em geral, o problema PET em ambientes regulados é um problema de programação não-linear inteira mista, o qual envolve algumas dificuldades, tais como um tempo prolongado para executar esse tipo de projetos, assim como a necessidade de uma técnica de otimização não-convexa. Além disso, devido à complicação dos problemas de otimização combinatória, e também por existir muitos mínimos locais neste caso, trata-se de um problema que exige tempos de...
Static and dynamic transmission network expansion planning under (n-1) security constraints
Keywords: Sistemas de energia eletrica; Energia eletrica - Transmissão; Automação; Algoritmos; Algoritmos genéticos; TABU (Linguagem de programação de computador); Electric power systems